A Rat Model with Multivalve Calcification Induced by Subtotal Nephrectomy and High-Phosphorus Diet - Liting Wang; Rining Tang; Yuxia Zhang; Zixiao Liu; Sijie Chen; Kaiyun Song; Yu Guo; Li Zhang; Xiaochen Wang; Xiaobin Wang; Hong Liu; Xiaoliang Zhang; et al. (Karger Publishers, 2020)
Background: Chronic kidney disease (CKD) with known valve calcification (VC) places individuals at high risk of cardiovascular disease. The study of VC in CKD is challenging due to the lack of a suitable research model. Here, we established a rat model of multivalve calcification induced by subtotal nephrectomy and a high-phosphate (HP) diet and analyzed the valve characteristics. Methods: We established a CKD model in Sprague-Dawley rats by performing 5/6 nephrectomy (5/6Nx) followed by feeding with chow containing different phosphate concentrations for 8, 12, or 16 weeks. The rats were divided into 4 groups: sham+normal phosphate (NP, 0.9% P), sham+high phosphate (HP, 2.0% P), 5/6Nx+NP, and 5/6Nx+HP. Serum creatinine (Scr), blood urea nitrogen (BUN), parathyroid hormone (PTH), calcium, phosphorus, and 24-h urine protein levels were investigated. Pathological examinations included histological characterization, safranin staining, Alcian blue staining, and von Kossa staining at different time points. Using nanoanalytical electron microscopy, we examined valves from rats in the 5/6Nx+HP and sham+HP groups and detected spherical particles using energy-dispersive spectroscopy (EDS) to observe microscopic changes in the valves. In addition, the calcified tissues were analyzed for phase and crystallization properties using an X-ray powder diffractometer. Results: The rats in the 5/6Nx+HP and 5/6Nx+NP groups presented with increased levels of Scr, BUN, and 24-h urine protein compared with those of the rats in the sham+HP and sham+NP groups. High levels of PTH were observed, and hematoxylin and eosin staining and immunohistochemistry for proliferating cell nuclear antigen showed parathyroid hyperplasia in rats in the 5/6Nx+HP group but not in the 5/6Nx+NP group. In rats in the 5/6Nx+HP group, extracellular matrix glycosylation was observed in the aortic valve in the 12th week and the mitral valve in the 16th week. In the 16th week, chondrocytes appeared in the aortic valve, as confirmed by immunofluorescence and Western blotting. Calcified particles mainly composed of phosphorus and calcium were observed in both the aortic and mitral valves by transmission electron microscopy and scanning electron microscopy (SEM). The main mineral component of the calcified aortic valve particles was hydroxyapatite [Ca5(PO4)3(OH)], as shown by X-ray diffraction. However, there were no obvious differences in heart function between rats in the 5/6Nx+HP and sham+HP groups. Conclusions: Our findings demonstrate that multivalve calcification is involved in CKD following 16-week HP and that hydroxyapatite [Ca5(PO4)3(OH)] is the main component of the calcified aortic valve particles of rats in the 5/6Nx+HP group.